Analisis Pola Asuh Orang Tua Terhadap Penggunaan Smartphone pada Anak Usia Dini Dimasa Pandemi Covid-19 di Kelompok BKB Vatika Samarinda - Ade al'fani; Rosdiana Rosdiana; Hanita Hanita (Universitas Ahmad Dahlan, 2022)
Backround: Parenting patterns during the pandemic are very much needed, both parents who work from home or who have started to go to work, need assistance and guidance when children are given smartphones so that children can follow the development of information media and technology positively. Objective: The purpose of this study was to analyze the type of parenting style for the use of smartphones in early childhood during the Covid-19 pandemic in the Vatika Family Development Group (BKB) in Sungai Kunjang District in 2021. Methods: The method used in this study was a qualitative method with a study approach. cases through interview and observation techniques on 6 informants, namely 3 parents of Vatika Family Development Group members who work, 2 caregivers who work with these parents, and 1 family member of the parents. Results: Based on the results of data analysis and discussion, in terms of smartphone use, the three main informants tend to be permissive because they allow children to use smartphones excessively, and there are no strict rules, controls, and supervision on the use of smartphones in their children so that children often play smartphones with intensity. tall one. This makes the child experience symptoms such as stinging in the eyes and pain in the neck. Conclusion: Parents do not provide strict and strict rules, but only situational, parents also lack supervision and assistance for children in using Smartphones. So that children play Smartphones with high intensity, so they are often seen experiencing eye fatigue